What Drives Post-Adoption Behavior in Relaunched Mobile Banking Apps? The Central Role of Satisfaction and the Conditional Effect of Technology Readiness - Prasetyo, Dimas Catur; Widuri, Rindang (International Review of Management and Marketing, 2026)
The rapid growth of digital banking has made mobile banking an important channel for enhancing customer experience and sustaining long-term usage. This becomes increasingly important during the early stage following a mobile banking relaunch, when users must adapt to new features and system environments. This study examines the effects of system quality, information quality, and service quality on user satisfaction, the moderating role of technology readiness, and the influence of satisfaction on word of mouth and continuance intention. Data were collected through an online questionnaire survey involving 329 active users of relaunched mobile banking applications from Indonesian top-tier commercial banks. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that system quality, information quality, and service quality positively influence user satisfaction, with service quality emerging as the strongest determinant. Technology readiness does not consistently moderate the relationships between quality dimensions and satisfaction, although it demonstrates a limited effect on service quality. In addition, user satisfaction positively influences word of mouth and continuance intention, while word of mouth further strengthens continuance intention. These findings highlight the importance of service quality in supporting user retention during the post-relaunch stage of mobile banking services.